Cancer Health Education Preferences among Miami-Dade County Construction Workers - Alberto J. Caban-Martinez; David J. Lee; Lora E. Fleming; Lourdes Loubriel; Syed M. Ahmed; Aracely Alicea-Clark; John Davis Clark III; Evelyn P. Davila (University of North Florida, 2009)
Construction work is a high-risk, transient occupation. Worksite outreach programs for cancer risk assessment are highly warranted because workers are exposed to both occupational and environmental carcinogens. We examined the feasibility and acceptability of conducting a paired cancer risk assessment and cancer prevention intervention using "lunch trucks" among construction worksites as the delivery mechanism. Among the 57 completed questionnaires from construction workers on a Miami-Dade County construction high-rise apartment building site, there were 50 (88%) males and 29 (51%) white Hispanics. Over 54% of the construction workers were current smokers of cigarettes, 3.5% chewed tobacco, and 19.3% smoked cigars. Of the current smokers, 80.1% expressed interest in quitting smoking, and 64.9% were willing to receive smoking cessation materials free of charge from a lunch truck at the construction site. Based on the results of this study, lunch trucks would be welcomed by construction workers as delivery mechanism to disseminate health education, cancer screening and smoking cessation information to this difficult to reach and highly underserved occupational group.